Foreigners in the probation system in Italy: Substantial discrimination and challenges - Ravagnani, Luisa (European journal of probation, 2024)
Foreigners in prison and probation are formally protected by the same rights that are applicable to Italian citizens but official statistics actually offer a different panorama. In fact, no social bonding, scarce or no financial resources, the lack of a permanent domicile and of any regular work activity, heavily affect the access of foreigners to probation regimes. The most evident and direct consequence is that more foreigners are kept inside prison walls than in the probation regime, while an indirect and still understudied aspect is the high percentage of suicides among foreigners in prison. The authors, after presenting the main difficulties experienced by foreigners in accessing the Italian probation system, consider the possible link with the suicide rate, and underline the need for further specific research into this worrying topic.